Modification of daytime compressional waves by the ionosphere: First results from OERSTED - Jadhav, Geeta; Rajaram, M.; Rajaram, R. (My University, 2001)
Ionospheric modulation of compressible hydromagnetic waves has been examined using the scalar magnetic field data obtained from the Oersted satellite and ground magnetic data from the Japanese sector. It is shown that the day side ionosphere introduces significant phase delays for frequencies in excess of about 20 mHz. The phase delay increases with frequency and with increase in the conductivity of the ionosphere. There is also an increase in the amplitude of the wave above equatorial day side ionosphere. The uniformly excellent coherence between the satellite and ground oscillations and systematically good correlation between the filtered time series at the two levels suggests that the compressible hydromagnetic waves are phase coherent over a wide range of latitudes.
Keywords: Daytime compressional waves; OERSTED; Magnetic field; Compressible hydromagnetic waves